Evidence for histamine release in chronic inducible urticaria – A systematic review - Kulthanan, Kanokvalai; Church, Martin K.; Grekowitz, Eva Maria; Hawro, Tomasz; Kiefer, Lea Alice; Munprom, Kanyalak; Nanchaipruek, Yanisorn; Rujitharanawong, Chuda; Terhorst-Molawi, Dorothea; Maurer, Marcus (Frontiers in Immunology, 2022)
Background: Chronic inducible urticaria (CIndU) constitutes a group of nine different CIndUs in which pruritic wheals and/or angioedema occur after exposure to specific and definite triggers. Histamine released from activated and degranulating skin mast cells is held to play a key role in the pathogenesis of CIndU, but evidence to support this has, as of yet, not been reviewed systematically or in detail. We aim to characterize the role and relevance of histamine in CIndU. Methods: We systematically searched 3 electronic databases (PubMed, Scopus, and Embase) for studies that reported increased serum or skin histamine concentration (direct evidence) or in vitro or ex vivo histamine release (indirect evidence) following trigger exposure. Results: An initial total of 3,882 articles was narrowed down to 107 relevant studies of which 52 were in cold urticaria, 19 in cholinergic urticaria, 14 in heat urticaria, 10 in contact urticaria, 7 each in solar urticaria and vibratory angioedema, 4 each in symptomatic dermographism and aquagenic urticaria, and 3 in delayed pressure urticaria. The results of our review support that histamine has a key pathogenic role in the pathogenesis of all CIndUs, but it is not the sole mediator as evidenced by the often poor relationship between the level of histamine and severity of symptoms and the variable clinical efficacy of H1-antihistamines. Conclusions: Histamine released from skin mast cells is a key driver of the development of signs and symptoms and a promising therapeutic target in CIndU.